Evidence of Authentic Deeds in Civil Disputes Related to Nominee Agreements on Ownership of Land Title Certificates - Trayama, Yoga; Adhari, Ade (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, in civil disputes related to nominee agreements regarding ownership of property certificates, the authentic deed can serve as a strong tool to ensure the validity of legal transactions. However, in reality, the implementation of authentic deeds is often hindered by doubts regarding their validity and compliance with applicable legal regulations, especially when involving foreign nationals (WNA) in land transactions. The aim of this research is to analyze the evidentiary power of authentic deeds in civil disputes involving nominee agreements on property ownership certificates and assess their effectiveness in the legal process. This article falls under normative juridical legal research with a statutory approach and case approach. The methodology used involves library research and qualitative analysis of regulations and relevant court decisions. The research concludes that authentic deeds have valid evidentiary power if they meet the formal, material, and external requirements, but can be canceled if they do not fulfill these conditions, and the notary who issues them may face sanctions. Notaries are responsible for ensuring the validity of the deeds they create, and if they cause harm to other parties, they can be held accountable according to applicable laws.